Mukhamandapa of Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Mandaleshwar Mahadev Temple is entered through a mukhamandapa (front porch). This is the view of the interiors of the mukhamandapa. It has two dwarf walls flanking the main entrance with two pillars on the outer side and two pilasters on the inner side. There are traces of kakshasanas (seat backs) on the mukhamandapa side walls. All these seatbacks are lost.